Ej blot til lyst. Konsultation og navigation i leksikografiske informationsværktøjer - Leroyer, Patrick (Nordiske Studier i Leksikografi, 2010)
The purpose of this article is to reassert the crucial importance of access to data in lexicographic information tools and, expanding on this, to establish the existence of two distinct lexicographic access modes – consultation and navigation. It is explained how the tools can be decalibrated when balance between user, access, and data is disturbed, and how access to data then is jeopardized. Taking online wine guides as a case in point, it is shown how such multifunctional information tools do benefit from a lexicographic design featuring both access modes.